Colpopexy and Pelvic Pain [11Q]. (May 2016) - Patel, Parin; Borahay, Mostafa A.
Abstract : INTRODUCTION: To examine the relationships between different colpopexy approaches and pre-operative and post-operative pelvic pain. METHODS: We extracted and analyzed data from Clinformatics™ DataMart (CDM) which is large national commercial insurance database. Using a retrospective cohort approach, data was collected from 9, 180 patients between the ages of 18–64 who underwent colpopexy between 2005 and 2012. Cases were selected using ICD-9 and CPT codes. Logistic regression analysis was performed using SAS software. Data were analyzed to determine relationships between pre-operative and post-operative pain, pain and concomitant hysterectomy and pelvic floor repairs, and pelvic pain and surgical approach. RESULTS: A total of 18, 092 patients underwent colpopexy between January 2005 and May 2012. Of which, 9, 180 met criteria and data from these cases was analyzed. Younger patients were more likely to have pre-operative pain. Vaginal colpopexy was associated with more postoperative pain compared to abdominal (OR 1.53, 95% CI 1.08–2.18). Concomitant hysterectomy was associated with less postoperative pain (OR 0.54, 95% CI 0.36–0.8). Concomitant vaginal repair were associated with more postoperative pain for those without prior pain (OR 1.85, 95% CI 1.21–2.83). CONCLUSION: Patients with pre-operative pain were more likely to undergo an abdominal colpopexy, have a concomitant hysterectomy, and have post-operative pain. Concomitant hysterectomy was associated with less pain, while concomitant vaginal repairs had no significant impact on post-operative pain. Randomized controlled trials are warranted. These findings will have significant impact on pre-operative patient counseling on surgery route.